Pengaruh Emotional Bonding Terhadap Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Kecamatan Tompobulu Kabupaten Bantaeng Tahun 2020 - Arifurrahman Burhanuddin; Andi Muhammad Multazam; Hasriwiani Habo (Journal of Muslim Community Health, 2021)
Background: Nutrisional problems incuding Stunting is malnutrision which is a major problem in the world, especially in Indonesia. According WHO, Stunting is calculated by comparing height or length children under five with the Z-score. Factors causing stunting event is very diverse, including parenting, age of weaning, history of breastfeeding, and bonding attachment between mother and baby will affect development of children. The purpose of this study was to analyze effects of Emotional Bonding to Stunting Events for children aged 24-59 months in Tompobulu District, Bantaeng Regency 2020. Methods: Observational analytic with cross sectional study. Implementation of research conducted in the District Tompobulu, Bantaeng. Selection of the place and sample using random cluster sampling technique. Results: Bivariate analysis showed that there was an effect of breastfeeding history on emotional bonding with a value p=0.034 (p<0.05). The age of weaning for emotional bonding, value of p=0.032 (p<0.05). Maternal parenting for emotional bonding, value of p=0.010 (p<0.05). Feeding patterns with emotional bonding get value p =0.044 (p<0.05). This means that there is a significant influence between history of breastfeeding age of weaning, maternal parenting, eating patterns with emotional bonding. Result the history of breastfeeding on the incidence stunting in toddlers were obtained with a value 0.022(p<0.05). The result of assessment on the factor of weaning age on the event of stunting in children showed p=0.046 (p<0.05). Maternal parenting for event of stunting in children showed p=0.029 (p<0.05). Feeding pattern toward the event of stunting in children p=0.022 (p<0.05). This means there is a significant effect between these factors and the event of stunting. The emotional bonding factors to effect of stunting in children, the value of p=0.046 (p<0.05), which means that there is a significant influence between these two factors. In regression test with multivariate analysisi, there were significant result on factors such as history of breastfeeding, age of weaning, maternal parenting and feeding patterns that affect emotional bonding factors. These factors also obtained significant result that affect the event of stunting in toddlers age 24-59 months. Emotional bonding factors to event of stunting, there were also significant results that affected the event of stunting in children. Conclusion of this study is there is effect of factors such as history of breastfeeding, age of weaning, maternal parenting, and feeding pattern with emotional bonding. Then, there is efferct of factors such as, history of breastfeeding, age of weaning, maternal parenting, and feeding pattern with Stunting event in children aged 24-59 months. Other than that, there is an effect of emotional bonding with stunting event in children aged 24-59 months in Tompobulu District, Bantaeng regency 2020.